Characterization of the Business Life Cycle from a Financial Perspective: A Study of Ecuadorian Manufacturing Firms - Karla González; Gabriela Duque; Angie Eras Cedillo; Adrian Siguencia (Journal of Technology Management & Innovation)
Financial statements play a critical role in business decision-making by providing a complete view of the financial structure of the company. Prior research has established a relationship between a firm's life cycle stage and factors such as dividend policy, capital intensity, inventory management, and the firm age. The objective of this study is to determine the characteristics that increase the probability that a company is in a life cycle stage, analyzing financial statements of 609 manufacturing companies in Ecuador in the period 2017 to 2019. A cluster study is conducted to determine whether the companies present differential characteristics according to the specific stage of the life cycle. Furthermore, the determinants of the life cycle stages are analyzed through a logistic regression model. Finally, using financial indicators, we examine the financial management of each group. The results reveal that companies in early stages (introduction and growth) face high levels of debt, while those that reach maturity prioritize dividend payments. Finally, companies in the decline phase present major challenges that compromise their level of income and their longevity over time. Although age shows a linear relationship with the different stages of the business life cycle, it should not be considered as the only explanatory variable.